Newest clinical trial results with anti-TNF and non-anti-TNF biologics for Rheumatoid Arthritis - Navarro-Millán, Iris (2013)
PURPOSE OF REVIEW: To highlight recent evidence from clinical trials of anti-Tumor necrosis factor (TNF) and non-anti-TNF biologics for rheumatoid arthritis (RA) focused on comparative clinical efficacy including safety outcomes and medication discontinuation. RECENT FINDINGS: Patients with RA are sometimes able to attain low disease activity or remission since the introduction of biologic therapy for RA. Biologics like anti-TNF, anti-interleukin-6 (IL-6), anti-CD20 and those that modulate T-cell co-stimulation have consistently shown good efficacy in patients with RA. Preliminary data from comparative efficacy studies to evaluate potential differences in between anti-TNF and non-anti-TNF biologics have shown little differences among these. There is ongoing work in comparative efficacy to answer this question further. SUMMARY: Biologic therapy in RA has significantly changed the course of RA in the last decade. Recently published CTs have been focused on comparative efficacy, cardiovascular safety of biologics and potential anti-TNF therapy discontinuation in patients with RA.